Accelerating uptake of household latrines in rural communities in the Volta Region of Ghana - Keraita, Bernard N.; Jensen, P.K.; Konradsen, Flemming; Akple, Maxwell Selase Kwasi; Rheinlander, T. (IWA Publishing, 2013)
This study was done in four rural communities in Ghana to assess uptake of household latrines. A total of 156 household interviews, 16 focus group discussions and 8 in-depth interviews with key informants were conducted. Study findings show that only 8.5% of households were using improved sanitation facilities with more than 75% of the households relying on open defecation and communal trench latrines. Knowledge of technological options was very limited and the cost for preferred latrines was unaffordable. Though health-related benefits motivated household latrine uptake, those related to personal security, privacy, social status and convenience were ranked higher. Sanitation uptake was constrained mainly by finances, poor sanitation promotion and general biophysical factors. High costs of latrine construction could be reduced by introducing cheaper technological options, using low-cost construction materials and labor contributions from households. Financing models like microcredit financing can also be explored and adapted for use in Ghana. We recommend the use of approaches aimed at behavior change while giving households a range of technological options such as community led total sanitation (CLTS). Hence, despite the low coverage of improved sanitation in rural Ghana, there exist real opportunities to accelerate sanitation uptake.